Effects of ondansetron on respiratory pattern and sensation of experimentally induced dyspnea - Martinez, José Antônio Baddini; Rocha, Fábio Senra; Sobrani, Elizabet; Galhardo, Fabíola Paula Lovetro; Terra Filho, João (São Paulo Medical Journal, 2002)
CONTEXT: Dyspnea remains a therapeutic challenge, especially in chronic respiratory conditions. Recent studies have shown that the induction of unpleasant dyspnea sensations activates areas in the insular cortex. OBJECTIVE: This study was designed to investigate the potential effects of ondansetron, a potent antiserotonin agent, on induced dyspnea sensation. TYPE OF STUDY: A randomized double blind study. SETTING: Pulmonary Function Laboratory of Hospital das Clínicas de Ribeirão Preto. PARTICIPANTS: Ten healthy male volunteers (mean age ± standard error = 23.1 ± 0.41 years) without respiratory diseases and showing normal spirometric tests. INTERVENTIONS: Uncomfortable breathing was induced in the volunteers on two different days, via the use of inspiratory resistors (loads of 0, 7, 14 and 21 cm H2O/l/sec) and breathholding, two hours after taking 8 mg of ondansetron (Ond) or placebo (Plac). MAIN MEASUREMENTS: Respiratory discomfort during breathing under loading was evaluated on a 100-mm visual analog scale. The maximum length of time of voluntary apnea was measured in seconds. RESULTS: The mean maximum voluntary apnea time did not differ between the ondansetron and placebo days (Plac = 96 ± 6.6 sec vs. Ond = 100 ± 7.9 sec). Ondansetron did not influence the dyspnea sensation induced by different inspiratory loads (0 cm H2O/l/sec: Ond = 1.4 mm ± 0.44 vs. Plac = 2.1 ± 0.85 mm; 7 cm H2O/l/ sec: Ond = 16.6 ± 2.74 mm vs. Plac = 13.7 ± 2.06 mm; 14 cm H2O/l/sec; Ond = 30.5 ± 4.50 mm vs. Plac = 27.1 ± 3.44 mm; 21 cm H2O/l/ sec: Ond = 50.3 ± 6.72 mm vs. Plac = 49.4 ± 6.72 mm). Ondansetron led to significant decreases in tidal volume under basal conditions and when breathing under the highest inspiratory loading (0 cm H2O/l/sec: Ond = 0.83 ± 0.26 l vs. Plac = 1.0 ± 0.28 l; 21 cm H2O/l/sec: Ond = 0.86 ± 0.23 l vs. Plac = 1.1 ± 0.22 l) CONCLUSION: The present results suggest that 5-HT3 receptors do not play an important role in the mediation of dyspnea sensations.